Preformation and Possible modification of Hotel Sarowar Solar Mini-Grid System Nepal on the basis of Maximum and Limit Power Point Tracking - Karna, Sanjay Lal; Jha, Ajay Kumar; Yadav, Kishori (Patan Prospective Journal, 2024)
Solar mini-grid systems (SMGS) are essential for promoting sustainable energy solutions by providing reliable and cost-effective electricity, especially in remote and off-grid areas. Their performance is influenced by factors such as seasonal variations, maintenance efficiency, and reliance on external power sources. This study evaluates the energy yield, consumption patterns, and performance ratio (PR) of the 140 kWp SMGS at Hotel Sarowar for 2022 and 2023 to assess its efficiency and sustainability. Data was obtained taken from Topsun Energy Pvt. Ltd., Sanobharyang, Nagarjun-02, Kathmandu, Nepal and processed using Sublime Text to clean and verify uniformity. Given the manageable dataset, calculations were performed in Excel. The findings reveal significant fluctuations, with an overall decline in energy yield in 2023 compared to 2022. For instance, energy yield in July 2023 dropped sharply to 10.23 MWh from 23.82 MWh in July 2022. August 2022 recorded a negative yield of -4.12 MWh, whereas August 2023 saw an improvement to 8.38 MWh. PR variations were also observed, with a notable increase from -15.2913 in August 2022 to 8.0191 in August 2023, reflecting system improvements. However, declines in PR during April, May, and November 2023 suggest potential inefficiencies. To address these fluctuations, integrating advanced Maximum Power Point Tracking (MPPT) and Limited Power Point Tracking (LPPT) techniques is recommended to optimize energy capture and ensure stable operation under varying environmental conditions.